The Role of Social Support in Promoting Resilience and Mental Well-Being - Afita, Laili; Nuranasmita, Tengku (CV. Creative Tugu Pena, 2023)
This study was inspired by evidence of a shortage of psychological well-being in society. The purpose of this study is to investigate empirically the relationship between anxiety, social support, and psychological well-being in society. And within the family, the husband and wife play an important role in managing the family to create a sakinah mawaddah warahmah family to understand the concepts or principles of mental health hygiene, which function to develop a healthy mentality or prevent the occurrence of mental illness in family members. The purpose of this study is to define and describe mental health, as well as to investigate the relationship between mental health and family well-being. This study employs library research or (library research). Bibliographic research is a type of study that is used to gather detailed information from numerous sources such as literature, books, notes, journals, and other references. Researchers can get information from scientific publications, scientific journals, and theses that are relevant to the subject being examined as a source of data. According to the findings of this study, a healthy mentality has a substantial impact on the success of a family that promotes community life. According to the findings of this study, the construction of a family life that has a personality that grows with a healthy mentality influences the formation of a prosperous family. All of the intended goals in a family can be properly accomplished with a healthy mentality. A healthy and affluent family with effective family functioning and strong relationships is a good beginning point for developing people' and society's mentalities. This is one of the elements that can contribute to the onset of mental diseases and have an impact on society. Keywords: Mental Well-Being, Resilience, Social Support